1984
DOI: 10.1021/jf00125a007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sodium chloride in meat by near-infrared diffuse reflectance spectroscopy

Abstract: Near-infrared (NIR) spectroscopy was used to measure the amount of salt (NaCl) in canned cured hams. Calibration with 20 samples produced a high correlation (r = 0.96) between salt contents determined by chemical analysis and by NIR using the second derivative of log (1/reflectance) values at 1806 nm. Salt contents of nineteen unknown samples were predicted with a standard error of prediction of 0.17% NaCl. Salted beef, salted fresh ham (uncured), and salted water model systems demonstrated that the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 0 publications
3
39
1
2
Order By: Relevance
“…IWAMOTO et al 15) and BEGLEY et al 16) reported that the NIR spectrum of water was shifted by the salt concentration.…”
Section: Resultsmentioning
confidence: 99%
“…IWAMOTO et al 15) and BEGLEY et al 16) reported that the NIR spectrum of water was shifted by the salt concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Begley et al [20] detected differences in the absorption bands of water at 1806 nm that were well correlated with different concentrations of NaCl in meat. A similar relationship between the total area of water absorption and crude protein content was found by Lugassi et al [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some work was done by using NIR infrared techniques for the determination of sodium chloride in raw meat (Begley, Lanza, Norris, & Hruschka, 1984), in cured salmon (Huang et al, 2001) and in smoked salmon (Lin, Cavinato, Huang, & Rasco, 2003). The applications of flow injection analysis and MID-IR to the cod fish desalting process merge to solve some of the local fish industry necessities of optimize the process itself and assure the final quality of the product.…”
Section: Introductionmentioning
confidence: 99%